IMPLEMENTASI REVENUE SHARING “MATTUNGKA SAPI” DITINJAU DARI ASPEK MUDHARABAH DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Syamsul, Syamsul; Abdullah, Muhammad Wahyudin; Awaluddin, Murtiadi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
Abstract: Revenue Sharing is a partnership concept carried out with a profit sharing system between one individual and another individual who runs a business or a company and another company in order to achieve mutually agreed goals.